Calcium alginate immobilized TiO2/ZnO beads for the removal of copper - Ravichandar, Shantini (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study was conducted to prepare calcium alginate (Ca-alginate) beads by immobilizing hybrid photocatalysts namely titanium dioxide, TiO2 and zinc oxide, ZnO. The calcium alginate beads were prepared by encapsulating different ratios of TiO2 and ZnO and their efficiency was further tested for the removal of copper (Cu) from water by using ultraviolet (UV) irradiation. Dark adsorption study was done without UV irradiation to determine the extent of Cu adsorption on the surface of the beads. The results showed that Cu was removed better in the presence of UV up to 90% than in the dark condition which was only about 55%. Suspended photocatalyst showed slightly higher photocatalytic activity compared to the immobilized photocatalyst in the removal of 60 ppm Cu. The effect of pH on Cu removal has been studied and the maximum removal efficiency of Cu was 98.7% at pH ~7. In the recycling study, Ca alginate immobilized TiO2/ZnO beads demonstrated good removal efficiency of Cu in all three cycles of use. Thus, the potential of Ca-alginate immobilized TiO2/ZnO beads as an environmentally friendly catalyst can be further developed for heavy metals removal from contaminated water.